(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The online game refers to games that are played over some form of computer network, typically on the Internet, in which you can connect with multiple players. Nowadays, online gaming is not only for the entertainment of the students but also for learning. According to some research, it helps teens to exercise their mind and cause them to explore the Internet. It enables the mind of the players to be more active, especially with puzzle-based games. It also helps the player to comeup with decisions in tight situations, especially with adventure games that require the players to be alert, active, and strategic. However, despite these benefits, playing online games becomes a necessity in their lives because it requires much of the player’s time, thereby leaving school activities and homework unattended. Academic performance declines when minimal attention is given to study. Thus, online gaming affects the academic performances of students positively and negatively. The researchers utilized a descriptive method design in collecting information. By implementing an in-depth research design such as this, a researcher can provide insights into the “why” and “how” of the research. The researchers chose 40 online gamers who are from General Academic Strand and conducted their research at Bestlink College of the Philippines. The researchers also used the purposive sampling technique. The instrument used in this research was a questionnaire that is anchored on the problem in Chapter 1. The researchers also used percentage and frequency distribution, weighted mean, ranking, and Likert’s five-point rating scale for the tabulated data. The results of the study showed that playing online games leads students away from stress, enhances teamwork, and makes them listen actively to class activities. In terms of their academic performance, students can relate to the lesson based on the online games they played. However, when students play games excessively, it may lead to addiction. This study proved that online gaming is beneficial for students, but they must know how to manage their time wisely. The support coming from their parents is also needed, especially in disciplining their children.